Physiological responses of tambaqui (Colossoma macropomum) fed diets supplemented with silage from fish and vegetables residues - Costa,M. N. F. (2024)
Abstract The demand for products to replace high-cost raw materials, such oil and fish meal, in the manufacture of feed for use in aquaculture, while also guaranteeing the nutritional quality of the diets, is increasing. Silage produced with fish and vegetables residues is a low-cost and efficient protein source. The objective of the present study was to evaluate the physiological and biochemical responses of tambaqui fingerlings fed four different levels of silage included in commercial feed with 28% crude protein, over two periods: 45 and 90 days. Each treatment was carried out over three replications, with 10 tambaqui in each 100 L experimental tank. At the end of each established period, blood samples were collected from five animals from each repetition to determine the hematological and biochemical variables. Body weight and total length, hepatosomatic and liposomal indices and hematocrit of specimens fed with diets supplemented with silage did not exhibit significant changes in both assessment period. After 45 days of feeding, the hemoglobin concentration increased when tambaqui were fed a diet including 20% silage. The red blood cell count, mean corpuscular volume and mean corpuscular hemoglobin did not change between treatments in either period. The total protein concentrations increased significantly in the plasma of tambaqui fed with diets with the inclusion of 5 and 10% of silage, evaluated after feeding for 45 days. It was found that the groups which had silage included in their diet did not exhibit significant alterations in the evaluated parameters, and the diet was therefore not consider harmful to the health of tambaqui. Therefore, the use of silage as a feed supplement during tambaqui farming is a sustainable alternative for producers, as it leads to a reduction of impacts of fish and vegetables waste disposal.